The association between intrauterine inflammation and spontaneous vaginal delivery at term: a cross-sectional study. - Michiel L Houben; Peter G J Nikkels; Grada M van Bleek; Gerard H A Visser; Maroeska M Rovers; Hilda Kessel; Wouter J de Waal; Leontine Schuijff; Annemiek Evers; Jan L L Kimpen; Louis Bont (PLoS ONE, 2009)
BACKGROUND:Different factors contribute to the onset of labor at term. In animal models onset of labor is characterized by an inflammatory response. The role of intrauterine inflammation, although implicated in preterm birth, is not yet established in human term labor. We hypothesized that intrauterine inflammation at term is associated with spontaneous onset of labor. METHODS/RESULTS:In two large urban hospitals in the Netherlands, a cross-sectional study of spontaneous onset term vaginal deliveries and elective caesarean sections (CS), without signs of labor, was carried out. Placentas and amniotic fluid samples were collected during labor and/or at delivery. Histological signs of placenta inflammation were determined. Amniotic fluid proinflammatory cytokine concentrations were measured using ELISA. A total of 375 women were included. In term vaginal deliveries, more signs of intrauterine inflammation were found than in elective CS: the prevalence of chorioamnionitis was higher (18 vs 4%, p = 0.02) and amniotic fluid concentration of IL-6 was higher (3.1 vs 0.37 ng/mL, p<0.001). Similar results were obtained for IL-8 (10.93 vs 0.96 ng/mL, p<0.001) and percentage of detectable TNF-alpha (50 vs 4%, p<0.001). CONCLUSIONS:This large cross-sectional study shows that spontaneous term delivery is characterized by histopathological signs of placenta inflammation and increased amniotic fluid proinflammatory cytokines.